Characteristics of Innovation System 4.0 in the Edge of the Fourth Industrial Revolution Four Relevant Cases in Germany - Lee, Byeouk-Gyu; Yeom, Myung-Bae; Sung, Eul-Hyun (International Journal of Engineering and Technology, 2019)
This paper deals with the characteristics of the Innovation System 4.0 at the edge of the fourth industrial revolution. It concerns the taxonomy of the Innovation System and, last but not the least, the description of features of the Innovation System. As a theoretical approach to the taxonomy of the Innovation System, a combination has been created herein between Innovation Process and Innovation System. It assumes that process in the broad sense is the totality of interrelated occurrences within a system. Because of the changes in the German Innovation System triggered by environmental problems and the Industry 4.0, four relevant cases have to verify according to the new core features. Although the theoretical foundation of the Innovation System 4.0, which is commenced in this paper, is still in its infancy, from a structural point of view, three aspects of this changed innovation system were highlighted: openness, participation and work-life balance. This could be a starting point for further discussions on the Innovation System 4.0.Â Â